Aplicações de temas em probabilidade e séries temporais no âmbito de iniciação científica de um aluno de graduação - BARBOSA, Breno de Castro (2024)
This work presents two applications of topics such as probability, statistics and time series to real problems in which the author participated as a researcher along with his supervisor. One of these is a direct application of his supervisor’s doctorate thesis and the other one is another problem, also in a topic that orbits the great area of probability and statistics. All applications shown in this work resulted in published short works/articles and were carried out between 2020 and 2023. The author aims to highlight, as well, the importance of research activities in a graduation course to the enrichment of the academic education of a student. This is done by recapitulating basic fundamentals of probability and time series theory, which are the foundations of the applications presented in this work. Besides, all the fundamentals presented here aim to turn this study accessible to an undergraduate student that is not initiated in the topic of this work.